Violations of Law and Human Rights Against the Sexual Exploitation of Children and Women - Alfian Eka Saputra; Ririn Hersa Yulianda; Meli Rispati (Formosa Journal of Applied Sciences, 2023)
Violation of law is an act that violates the norms and rules that have been made to say human behavior. Human rights are a right inherent in humans from humans in the womb until humans are gone. The purpose of this research is to be Uckukaiii Bakahana the law of the exploitation of children and women as well as the efforts of the collection which is carried out by collecting data from various literature based on literature research that is concluded that the exploitation of children in Indonesia has re-increased in 2021 in many young people. In order to prevent the exploitation of children, saahya and the nokauti is one of the numbers.